MANAJEMEN LABA PADA PERUSAHAAN GO PUBLIC DI INDONESIA - Rina Trisnawati; Wi yadi; Noer Sasongko (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2012)
Information about earning is used as indicator of management performence. The Flexibility for choosing accounting method gives opportunities for managers choose policies to maximize their utility and market value of their firms. Healy and Wahlen (1998) considered earnings management as an act of misleading and deceiving shareholders. The purpose of this study was to analyze the earnings management as an earnings management pratices in indonesiaan capital market, that is the shariah index (III) and conventional index (LQ-45) These samples were 153 and 187 companies listed in indonesian stocks exchange from 2004-2010 periods. The results indicated the earnings management (DACC) in jakarta Islamic Index are 0.0962 (2004) ;0.11104 (2005): 0.03673(2006);0.20509(2007); 0.087056(2008); 0.045405(2009) and 0.100421 in (2010) the result also showed that the pattern of earnings management in III was to maximize its profit the earnings management(DACC) in LQ45 are 4,011 (2004); 0.1544 (2005) ; -0.24745 (2006); 0.54136 (2007); 0,87887 (2008) ; -0.51586(20090 and -2.52645 in (2010). The variation pattern of earning management value takes place taxes place during these periods the result showed that the average value of accruals (DACC) on the companies listed in the conventional index is 0.8042 and the average value of accrual (DACC) on the companies in the shariah index is 0.09831 . Stastiscal test showed that there was not significant differences in earnings management pratices(DACC) between companies in the shariah index and conventional index (prob.value=0.335). It means that earnings management praticies which tend to increase the profit made by the companies in the conventional index more than the companies in the shariah index. Earnings management perspective used in this study is accrual basis. For further research, earnings management needs to be reviewed by integrated model to determine the intergrated earnings management value by accrual and real methods.